Pengaruh Penggunaan Twitter Terhadap Keberanian Berkomunikasi Dakwah Pada Mahasiswa KPI Institut Agama Islam Al-Zaytun Indonesia Angkatan 2020 - Saskia Putri Nabila; Supriadi Supriadi; Elang Bakhrudin H (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2026)
This study examines the role of social media, particularly Twitter, as a digital da’wah medium that is fast, interactive, and easily accessible to users. However, the extent to which the use of Twitter can enhance communication confidence among students still requires empirical validation. The focus of this research is to evaluate the effectiveness of Twitter use in influencing students’ communication abilities, especially in delivering da’wah messages. The purpose of this study is to analyze the effect of Twitter usage on the communication confidence of students from the 2020 cohort. A quantitative approach was employed using a survey method. Data were collected through a structured, scale-based questionnaire, in accordance with the positivistic research paradigm that emphasizes objective and measurable hypothesis testing. The research population consisted of 62 students, from which 38 respondents were selected using proportionate stratified random sampling to ensure representation across all population strata. The findings reveal that the use of Twitter has a significant effect on the communication confidence of KPI IAI Al-Azis students from the 2020 cohort in delivering da’wah messages. Regression analysis results show a significance value of 0.050 < 0.05, with a Pearson correlation coefficient of 0.614, indicating a strong relationship. These results suggest that the more frequently students engage with Twitter, the greater their confidence in expressing and disseminating da’wah messages through various digital formats such as text, images, and videos. Twitter thus provides an expressive platform that fosters interaction, encourages participation, and strengthens students’ digital da’wah communication skills.